Uploaded by mtobob ![The End wasn't The End - Found a new home after the great exodus of 2012 The End wasn't The End - Found a new home after the great exodus of 2012](https://derpicdn.net/badges/2016/8/22/25688c9abdc3ce6e902815.svg)
960x540 00:03.50 GIF 921 kBInterested in advertising on Derpibooru? Click here for information!
![Ministry of Image - Fanfiction Printing](https://derpicdn.net/spns/2019/6/25/1923144237214237213052773547002644199840.png)
Help fund the $15 daily operational cost of Derpibooru - support us financially!
Description
No description provided.
Tags
+-SH safe2285135 +-SH artist:jan663 +-SH oc1012887 +-SH oc only741308 +-SH oc:canni soda459 +-SH earth pony552802 +-SH pony1714656 +-SH galacon980 +-SH galacon 201332 +-SH g42126632 +-SH animated133475 +-SH captain obvious743 +-SH clothes680890 +-SH earth pony oc29449 +-SH fancy mathematics263 +-SH formal wear394 +-SH mascot1681 +-SH math1007 +-SH necktie13212 +-SH numbers1516 +-SH paper5073 +-SH solo1506334 +-SH suit9872
Loading...
Loading...
Also:
x, y := 4, 4
y + 0 = x
x > y
x, y := 6, 9
y + (-3) = x
x > y
Oops?
You forgot to say that
that number
must be greater than0
.And first you need to prove that 1 + 1 even equals 2 if you’re going to take that route.
HI PEWDIE!
Everything is sexier in French.
Bitches if you may….
From the definition of addition s(0) + s(0) = s(0 + s(0)). Axiomatically, for all x, x + 0 = x. From this, 0 + 0 = 0, and if 0 + x = x, then 0 + s(x) = s(0 + x) = s(x), and so 0 + x = 0 for all x. Thus, 1 + 1 = s(0) + s(0) = s(0 + s(0)) = s(s(0)) = 2. For any numbers x and y, x > y only if there exists a number such that y + that number = x. Since 1 + 1 = 2, 2 > 1.
two is greater than one!
But 2 dodges and counterattacks combined 1 with an arrow blast.
A croissant would have been more appropriate but suuure lets go with banana o_0
And 4 + 1 = MOO
I think you meant to say 2+2 = fish